Analisis Kesulitan Belajar Siswa pada Mata Pelajaran Bahasa Indonesia Kelas V SD - Lestari, Pitri Weni; Imansyah, Farizal; Kuswidyanarko, Arief (Indonesian Research Journal on Education, 2022)
Analysis of Students' Learning Difficulties in Indonesian Language Subjects in Class V Elementary School. This study aims to describe the factors thatcause learning difficulties and efforts to overcome learning difficulties in Indonesianlanguage subjects in fifth grade elementary school. The method used by theresearcher is a qualitative descriptive method. The sources of data in this study werethe answers to the action test, the analysis of learning activities, the results oflearning interviews and the results of observations. The data analysis techniqueused is data collection, data reduction, data presentation and conclusions or data verification. The result of this research is thatstudents are slow in reading and stillhave difficulty in writing in spelling, punctuation, syllables, sentence use and capitalletters. There are several factors that cause students to have learning difficulties, donot understand the material presented by the teacher, are slow in reading, still often use local languages and the efforts made to overcome learning difficulties providespecial guidance and direction to students who have learning difficulties duringbreaks and provide guidance to parents to help their children read at home.